Long-acting inhaled anticholinergic therapy improves sleeping oxygen saturation in COPD. - McNicholas, W; Calverley, P; Lee, A; Edwards, J (2004)
Oxygen desaturation occurs during sleep in severe chronic obstructive pulmonary disease (COPD), especially during rapid eye movement (REM) sleep, due to hypoventilation and ventilation-perfusion mismatching, but the possible contribution of airflow limitation is unclear. In a randomised, placebo-controlled, double-blind study of severe, stable COPD patients, the authors compared 4 weeks treatment with a long-acting inhaled anticholinergic agent (tiotropium), taken in the morning (tiotropium-AM), or in the evening (tiotropium-PM), on sleeping arterial oxygen saturation (Sa,O2) and sleep quality. Overnight polysomnography was performed at baseline and after 4 weeks treatment. A total of 95 patients with awake resting arterial oxygen tension < or = 9.98 kPa (75 mmHg) were randomised, with a mean age of 66.4 yrs and mean forced expiratory volume in one second (FEV1) of 32% predicted. A total of 80 patients completed the study, of which 56 fulfilled the polysomnographic criterion of at least 2 h sleep in both sleep study nights and represent the group analysed. Tiotropium significantly improved spirometry compared with placebo. Both tiotropium-AM and tiotropium-PM groups had higher Sa,O2 during REM than placebo (+2.41% and +2.42%, respectively, and both pooled and tiotropium-PM groups had higher Sa,O2 during total sleep time (+2.49% and +3.06%, respectively). End-of-treatment FEV1 correlated with Sa,O2 during REM sleep, however, tiotropium did not change sleep quality. Sustained anticholinergic blockade improves sleeping arterial oxygen saturation without affecting sleep quality.